Supporting Vaccination on TikTok During the COVID-19 Pandemic: Vaccine Beliefs, Emotions, and Comments - Wang, Xiaopei; He, Renyi (Frontiers in Psychology, 2022)
TikTok has been one of the most important social media platforms where pandemic-related information converged and has been disseminated. However, how vaccination-related visual content, particularly pro-vaccine videos, influences audiences remains unclear. Using Betsch et al.’s 5C model and Ekman’s basic emotion model, we identified 200 trending videos under the hashtag #vaccine on TikTok, and examined the types of vaccine-related beliefs and emotions expressed in videos and the relationship between beliefs, emotions, and supportive comments. Confidence and joy were the most frequently expressed belief and emotion, respectively; confidence (B = 14.84, P < .05), surprise (B = 11.29, P < .05), and sadness (B = 37.49, P < .01) predicted the number of supportive comments. This study expands the 5C framework of vaccine hesitancy into the analysis of pro-vaccine content on social media and offers detailed insights into the specific type of beliefs and emotions and their effects. Practical implications regarding how to address vaccine hesitancy are discussed.